2022
DOI: 10.1111/1556-4029.15147
|View full text |Cite
|
Sign up to set email alerts
|

Lack of fermentation in antemortem blood samples stored unstoppered in various locations

Abstract: A common defense challenge when antemortem blood ethanol results are presented at trial is the assertion that ethanol was formed in the blood tube after the blood draw through fermentation of the blood glucose by Candida albicans (C. Albicans). In contrast, decades of research into the stability of ethanol in antemortem blood collected for forensic purposes have consistently shown that any analytically significant change in ethanol concentration is a decrease and initially, ethanol-negative blood remains ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The question about how much, if any, sodium fluoride is necessary to include in stored antemortem blood has been brought up in response to a manufacturing error in which the preservative was not added to the blood collection tubes [16]. Antemortem ethanol-free blood collected from individuals using lavender-top Vacutainer® tubes without sodium fluoride and stored at either room temperature, 22°C, or elevated temperature, 37°C, for a month remained ethanol-free [17]. Early research reported a significant difference in ethanol stability between blood with and without sodium fluoride when stored refrigerated in RSA cups or glass ampoules for 4 or 8 weeks [8].…”
mentioning
confidence: 99%
“…The question about how much, if any, sodium fluoride is necessary to include in stored antemortem blood has been brought up in response to a manufacturing error in which the preservative was not added to the blood collection tubes [16]. Antemortem ethanol-free blood collected from individuals using lavender-top Vacutainer® tubes without sodium fluoride and stored at either room temperature, 22°C, or elevated temperature, 37°C, for a month remained ethanol-free [17]. Early research reported a significant difference in ethanol stability between blood with and without sodium fluoride when stored refrigerated in RSA cups or glass ampoules for 4 or 8 weeks [8].…”
mentioning
confidence: 99%